1998
DOI: 10.1037/0096-1523.24.2.481
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frequency of judgement and the type of trials on covariation learning.

Abstract: This study showed that accuracy of the estimated relationship between a fictitious symptom and a disease depends on the interaction between the frequency of judgment and the last trial type. This effect appeared both in positive and zero contingencies (Experiment 1), and judgments were less accurate as frequency increased (Experiment 2). The effect can be explained neither by interference of previous judgments or memory demands (Experiment 3), nor by the perceptual characteristics of the stimuli (Experiments 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 51 publications
(104 reference statements)
0
94
0
2
Order By: Relevance
“…This effect implies that making a judgement is a crucial determinant of judgement accuracy (Catena et al, 1998;Maldonado et al, 1999). We submit that various singlemechanism theories cannot account for this effect and instead propose an account that includes two mechanisms that operate in a serial manner: The first of these computes the statistical relationship, and the second one integrates this information with any other information or beliefs about the task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect implies that making a judgement is a crucial determinant of judgement accuracy (Catena et al, 1998;Maldonado et al, 1999). We submit that various singlemechanism theories cannot account for this effect and instead propose an account that includes two mechanisms that operate in a serial manner: The first of these computes the statistical relationship, and the second one integrates this information with any other information or beliefs about the task.…”
Section: Discussionmentioning
confidence: 99%
“…These models could yield different predictions, however, if they assumed that the judgement frequency affects learning rate parameters. This change might, for example, explain the differences frequently found at the end of a given period of training (i.e., a response mode effect, Catena et al, 1998), as performance reached will depend on these parameters (Allan, 1993). After a non-exhaustive search in the learning rate parameter space to fit the data for group HH and group LL in Experiment 1, we found that Markman's (1989) model predicted significant differences between a and d versus b and c trials not only in the high-but also in the low-frequency conditions (see Table 1).…”
Section: Single-mechanism Modelsmentioning
confidence: 99%
“…It does not seem reasonable to compare prediction and causation dependent variables that lie on different measuring scales and are collected at different points in time during the experiment. Indeed, it has long been shown that the moment when a judgment is collected and the frequency with which it is collected can change dramatically the participants' responses (e.g., Catena, Maldonado, & Cándido, 1998;Collins & Shanks, 2002;Matute, Vegas, & De Marez, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also demonstrated a wide variety of critical learning effects using different versions of this task (e.g., Allan, Siegel, & Tangen, 2005;Buehner & Cheng, 1997;Catena, Maldonado, & Cándido, 1998;Cobos, López, Caño, Almaraz, & Shanks, 2002;Dickinson & Burke, 1996;Karazinov & Boakes, 2004;Le Pelley & McLaren, 2001;Vila & Rosas, 2001;Waldmann, 2001;Wasserman, 1990).…”
Section: Allergiesmentioning
confidence: 99%